A computational study of bio-chemo-mechanics of thrombus-laden aneurysms. (February 2023) - Virag, Lana; Horvat, Nino; Karšaj, Igor
Abstract: The role of intraluminal thrombus (ILT) in abdominal aortic aneurysm (AAA) development has been controversial for decades, yet the researchers and clinicians agree that thrombus is not an innocent bystander in disease progression. In an effort to increase our understanding of its role, in this work, we present a bio-chemo-mechanical mathematical model of thrombus-laden aneurysms. Unlike all previous finite element studies, where AAAs grow due to prescribed irreversible time-dependent elastin degradation, in this study, protein degradation depends on protease activity. Enzymes degrading collagen and elastin are believed to come from the luminal layer of intraluminal thrombus and the increasing area of chemotactic vasa vasorum in the wall. The geometrical and structural spatiotemporal changes in the aneurysmal wall at the apex and shoulder region of the thrombus-laden aneurysm are explained in detail. Furthermore, we show that later ILT formation is more perilous than its early deposition, despite lower peak protease activity and related extracellular matrix degradation. Interestingly, the radial growth rate is slightly slower for fully thrombosed AAAs compared to the partially thrombosed ones, however, their axial growth is much more pronounced. Additionally, we show that thrombus deposition greatly impacts the aneurysmal sac shape and volume.